APIMONITORING OF HEAVY METALS OF THE REGIONS OF THE NIZHNY NOVGORD REGION DIFFERING IN ECOLOGICAL INTENSITY - V. V. Yagin; D. A. Homutov; V. .. Petrov; A. E. Homutov (Вестник Мининского университета, 2017)
The comparative assessment of the content of heavy metals in samples of honey, wax, propolis, bee sting and bodies of the bees received in the different regions of the Nizhny Novgorod Region differing in ecological intensity is carried out. The comparative characteristics of heavy metals in bee products obtained in apiaries located near the federal highway and in the forest area. It is shown that the levels of lead, cadmium, strontium, zinc and copper in the samples of bee products is higher in samples obtained at apiaries located near the motorway. The maximum difference between the zones account for zinc, which is 5-9 times higher in samples near the motorway teachings.